Basalt fibre reinforced polymer composite filled with nano silica for green truck body panel - Muslim, Mohamad Asrofi; Jumahat, Aidah; Abdullah, Shahrul Azam (Universiti Teknologi MARA, Kedah, 2023)
The truck body panel industry ensures commercial vehicles' structural integrity and safety within the automotive sector. The composites are manufactured using manual lay-up and vacuum silicon mould techniques. These composites utilise basalt/glass fibres for reinforcement and polyester resin as the matrix. The primary aim is to assess the benefits of incorporating nano-silica to enhance the impact properties of these materials at varying concentrations (1%, 3%, and 5% by weight) of nano silica. Experimental tests were conducted to evaluate impact properties, and the results were compared with those of Carbon Tech Global (CTG), an industrial reference sample. The visual impact findings indicate that adding 1% nano-silica to basalt and glass fibre-reinforced composites (BFRPC/GFRPC) improves impact characteristics by showing the most samples that absorbed energy. These promising outcomes suggest potential practical applications in the automotive sector. These enhancements underscore their suitability for increased utilisation in commercial vehicles and establish them as viable choices for truck body panel materials.